Production and characterization of taffy candy from collagen of chicken feet. - Fernando, Rezzy Lee B.
The global market for confectioneries is driven by the introduction of new products with innovative flavors and with use of high functional and healthy ingredients. This study generally aimed to utilize collagen extracted from chicken feet for the production of chewy confectionery product, particularly taffy candy. The use of collagen as an ingredient in a food product can enhance the quality, nutritional and health value of these products. This study used Ramdomized Complete Block Design (RCBD) experiment in the extraction of collagen from chicken feet. The different chicken feet to water (w/v) ratio that were utilized in the production of taffy candy were 1:1, 1.5:1, and 2:1. All formulations were characterized by physico-chemical and microbiological analysis. One-way ANOVA and Post Hoc test (Tukey) were used as an aid for statistical analysis of various assays. The results obtained showed that at P=0.05, all formulations significantly differed with each other in terms of physico-chemical analysis. Treatment 1 had the highest moisture content (10.74%) and water activity (0.577) but had the lowest protein (0.79%) while Treatment 3 had the highest protein (1.13%) and had the lowest moisture content (6.10%) and water activity (0.458). For Treatment 2, the %MC (8.96), aw (0.509) and %protein (1.03) values were in between of the two treatments. The hardest among the three was Treatment 3, which had a value of 3086 g. Microbiological assessment by Total Plate Count (TPC), showed lower microbial load in Treatment 2 and 3 than Treatment 1 but all were safe for consumption. The overall acceptability of the most preferred formulation (Treatment 2) was rated by a panel of 45 evaluators with 7.47 which means ?like very much?. The potential use of chicken feet collagen for taffy canfy was its provision of the texture and stability to the product.